Pathways to forest wealth in Nepal. (15th May 2019) - Nuberg, I. K.; Shrestha, K. K.; Bartlett, A. G.
ABSTRACT: Nepal is one of the leading countries embracing community forestry with about 45% of households being members of community forest user groups. However, there has been a failure to deliver the full potential of forest wealth because of a lack of proper silvicultural management, a constraining policy environment and a complex socio-institutional context. Meanwhile, mid-hill agriculture has not kept pace with the changing economy and out-migration. Food insecurity is rife in a landscape of under-utilised forests and under-utilised land. Australian development assistance between 1978 and 2006 supported the establishment of 21 000 ha of community forests and significant contributions to community forest institutions. In the light of the under-performance of this sector, the Australian Centre for International Agricultural Research established the project Enhancing Food Security and Livelihoods through Agroforestry and Community Forestry in Nepal, locally known as EnLiFT, which ran from 2013 to 2018. This paper aims to explain Australia's contribution to Nepal's forestry, with a focus on more recent achievements supporting pathways to realise the potential wealth in Nepal's forests. It begins with an outline of the early Australian support and origins of community forestry in Nepal via the Nepal–Australia Forestry Project, and then the current status of community forestry. It then describes the research process of the EnLiFT project starting with new conceptual models and methods such as: (1) the Pathways Approach to link forest and food security; (2) the EnLiFT Bioeconomic Model of the Farm-Forest Interface; (3) the Silvo-Institutional Model for Scientific Forest Management; (4) Active and Equitable Forest Management; (5) Rapid Silvicultural Appraisal; (6) the Strategic and Inclusive Planning process and (7) EnLiFT Policy Labs. We also highlight many significant development impacts of EnLiFT. The demonstration and training of silvicultural methods released considerable forest wealth into the community. This occurred around the time of the 2015 earthquake when timber was in need for reconstruction. It was also associated with the re-vitalisation of a defunct sawmill by facilitation of community-private partnership. It was responsible for turning the public debate from resistance to acceptance of scientific forest management. It also developed inclusive planning processes for the revision of operational plans of community forests. On privately owned land, EnLiFT demonstrated: (1) the possibility for marked and rapid changes in livelihoods from relatively simple agroforestry interventions based on horticultural commodities and tree fodders; (2) an even greater potential for livelihood enhancement through private forestry and (3) articulated the current institutional and regulatory constraints on sale of trees from private land. We conclude by highlighting the contributions of EnLiFT in policy debate which led to policy outcomes that further the improvement of community forestry, agroforestry and bringing under-utilised land back into productive use.